The ECR LTSP management tool (ELM tool) - Flores, Michael Edward S. (2005)
The previous setup in the Engineering Computer Room (ECR) was very manual. Users had to secure a prepaid card from the administrator and have it signed before they can use the facilities. ECR volunteers also had to watch the users and tell them when their time is up. The ECR LTSP Management Tool (ELM Tool) was developed an automated ticketing system for the ECR. It aims to upgrade the current setup, by providing a convenient system for the users and the administrator. The ELM Tool will provide an interface between the users and the administrator so that billing would be done automatically. The program shall keep track of users' time consumption and send an automated call when their time expires. The administrator can also communicate with the users and extend a specific user's time with a single click. The ELM Tool is designed to run under the Linux Termina Server Project (LTSP). The LTSP is a relatively new technology that provides a networking system that enables diskless clients to log-on to a powerful server, and make use of the server's resources.